A Uchl1‐Histone2BmCherry:GFP‐gpi BAC transgene for imaging neuronal progenitors. Issue 12 (21st October 2013) - Wiese, Carrie B.; Fleming, Nicole; Buehler, Dennis P.; Southard‐Smith, E. Michelle
<x xml:space="preserve">Abstract</x> Summary: Uchl1 encodes the protein gene product 9.5 antigen (PGP9.5) that is a widely used to identify migrating neural progenitors in the PNS, mature neurons of the central and peripheral nervous systems, as well as neuroendocrine cells. To facilitate analysis of developing peripheral neurons, we linked regulatory regions of Uchl1 carried within a 160kb bacterial artificial chromosome (BAC) to the dual fluorescent reporter H2BmCherry:GFP‐gpi. The Uchl1‐H2BmCherry:GFP‐gpi transgene exhibits robust expression and allows clear discrimination of individual cells and cellular processes in cranial ganglia, sympathetic chain, the enteric nervous system (ENS), and autonomic ganglia of the urogenital system. The transgene also labels subsets of cells in endocrine tissues where earlier in situ hybridization (ISH) studies have previously identified expression of this deubiquinating enzyme. The Uchl1‐H2BmCherry:GFP‐gpi transgene will be a powerful tool for static and live imaging, as well as isolation of viable neural progenitors to investigate processes of autonomic neurogenesis. genesis 51:852–861. © 2013 Wiley Periodicals, Inc.